If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(x + 6) = 6(1 + -1x) + -4x Reorder the terms: -4(6 + x) = 6(1 + -1x) + -4x (6 * -4 + x * -4) = 6(1 + -1x) + -4x (-24 + -4x) = 6(1 + -1x) + -4x -24 + -4x = (1 * 6 + -1x * 6) + -4x -24 + -4x = (6 + -6x) + -4x Combine like terms: -6x + -4x = -10x -24 + -4x = 6 + -10x Solving -24 + -4x = 6 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. -24 + -4x + 10x = 6 + -10x + 10x Combine like terms: -4x + 10x = 6x -24 + 6x = 6 + -10x + 10x Combine like terms: -10x + 10x = 0 -24 + 6x = 6 + 0 -24 + 6x = 6 Add '24' to each side of the equation. -24 + 24 + 6x = 6 + 24 Combine like terms: -24 + 24 = 0 0 + 6x = 6 + 24 6x = 6 + 24 Combine like terms: 6 + 24 = 30 6x = 30 Divide each side by '6'. x = 5 Simplifying x = 5
| r^2-r=36+4r | | 4x+7=3x-2 | | 7(1-2x)-8(x+2)=-5x-8x | | 5x+8y=-32 | | -5(x-4)=2(-2x+5)-5 | | 3(x-7)=12 | | 3(5n-3)=-(n-7) | | x^3-5x^2=36x | | x^2-(x+25)=(x+2)(x-2) | | -3(1-2n)-7n=-6-8(n+4) | | (x-3)(x^2-3x+9)=0 | | 2m^2+10=0 | | -49-35x=7(-5x+8) | | 2x^3+(-13x^3)=x | | 2(x^2-5)=2x^2+x-50 | | -(1-6x)=-2(-3x+3) | | 2(8+7r)=6(2+3r) | | 3x+5= | | 5(x-3)-(x-5)=x-1+1+2x | | -3(x+6)-6x=-2(1+5x) | | 7=2+5(z-2) | | 2x+8x=2(x+1)+5(8x+6) | | 12x+23=5x+205 | | 4(2+n)=-2(n+4)+4 | | 161-4x=23x+23 | | 4(2+n)=-2(n+4 )+4 | | 7-8x=22-15x | | 4(2+n)=-2(1+5n) | | -155-8x=9x+15 | | 2+10x=92+x | | 4(2+n)=-2(1+5x) | | 2x+11=-9-8x |